Organization of Theaters Management Processes (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article presents the main methods of managing theatrical activities. The necessary requirements for the management organization, organizational and functional structures of theaters, methods based on effective management using management criteria, and their specifics are highlighted.